KUR`AN-I KERİM AÇISINDAN İBADETLERİN İNSAN DAVRANIŞLARINA ETKİSİ - ORUÇ, CEMİL (Fırat Üniveristesi, 2005)
ABSTRACTThis article deals with the concept of workship and it?s usage in the holyQur?an. There are many verses available in the Qur?an about the concept of theworkship and behaviour. These verses being understood correctly is depended to thekonown very well of human and Qur?an.The first part of this this study aimed to explaine some word as soul,religion and education.thirty part, it was explained the most importent workships in theÃ¸Q WKHQur?an. On the other hand the modern psycholagy?s opinions were added to.As a rasult, it was stressed that workship and behaviour relations and it wastold to be understood workship will make to be understood.Key WordsQur?an, workship, behaviour, soul, the namaz, alms, fast, pilgrimate.
On Account of Qur`an the worship, s effections on the human behavior
Keywords: Din